Protectins PCTR1 and PD1 Reduce Viral Load and Lung Inflammation During Respiratory Syncytial Virus Infection in Mice - Walker, Katherine H.; Krishnamoorthy, Nandini; Brüggemann, Thayse R.; Shay, Ashley E.; Serhan, Charles N.; Levy, Bruce D. (Frontiers in Immunology, 2021)
Viral pneumonias are a major cause of morbidity and mortality, owing in part to dysregulated excessive lung inflammation, and therapies to modulate host responses to viral lung injury are urgently needed. Protectin Conjugates in Tissue Regeneration 1 (PCTR1) and Protectin D1 (PD1) are Specialized Pro-resolving Mediators (SPMs) whose roles in viral pneumonia are of interest. In a mouse model of Respiratory Syncytial Virus (RSV) pneumonia, intranasal PCTR1 and PD1 each decreased RSV genomic viral load in lung tissue. Concurrent with enhanced viral clearance, PCTR1 administration post-infection decreased eosinophils, neutrophils and lung NK cells, including NKG2D+ activated NK cells, in the lung. Intranasal PD1 administration, given after RSV infection, decreased lung eosinophils and Il-13 expression. PCTR1 increased lung expression of cathelicidin anti-microbial peptide and decreased interferon-gamma production by lung CD4+ T cells. PCTR1 and PD1 each increased interferon-lambda expression in human bronchial epithelial cells in vitro and attenuated RSV-induced suppression of interferon-lambda in mouse lung in vivo. Liquid chromatography coupled with tandem mass spectrometry of RSV-infected and untreated mouse lungs demonstrated endogenous PCTR1 and PD1 that decreased early in the time course while cysteinyl-Leukotrienes (cys-LTs) increased during early infection. As RSV infection resolved, PCTR1 and PD1 increased and cys-LTs decreased to pre-infection levels. Together, these results indicate that PCTR1 and PD1 are regulated during RSV pneumonia, with overlapping and distinct mechanisms for PCTR1 and PD1 in the resolution of viral infection and its associated inflammation.